Pauline dogmatics : the triumph of God's love - Campbell, Douglas A. (Douglas Atchison), 1961- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2020)
"Douglas Campbell here offers a Pauline Dogmatics that moves to how Paul saw God revealed in Jesus and culminates in emphasizing the implications of Paul's gospel in his world and today"--
Jesus -- Vigilance -- A God of love -- A God of story -- Resurrection and death -- Resurrection and sin -- Defending resurrection -- Election -- A learning community -- Leaders -- Love is all you need -- Loving as giving -- Loving as faithfulness -- Loving as peacemaking -- Loving as enjoying -- An apostolic foundation -- Defining the other -- The triumph of love -- Mission as friendship -- Missional diversity -- Evaluating paganism -- Transforming paganism -- Request ethics -- Rethinking creation -- Navigating sex and marriage -- Navigating gender -- Beyond colonialism -- Beyond supersessionism -- The pastor's wisdom.
Includes bibliographical references (pages 745-769) and indexes.
Keywords: Bible. -- Theology; Bible. -- Criticism, interpretation, etc; Love -- Biblical teaching